Effects of oil palm leaf extract in enhancing memory, improving bone mass, and reducing anxiety in ovariectomised rats - Ahdab, Bakhsh (2012)
Long term estrogen deficiency in women often leads to decrease in cognitive function and bone density. This study reports on the in vivo mineral bone-density, anxiety and cognition enhancing effects of the supplementation with phytoestrogenic oil palm leaves extract (OPL) in normal and estrogen-deficient ovariectomized female Sprague Dawley rats which was compared to green tea (GT). The rats were divided into five experimental groups: (1) Normal rats (control N); (2) ovariectomized rats (OVX control); and OVX rats supplemented with either (3) green tea (2.0% w/v) [OVX+GT]; (4) 150 mg OPL/kg body weight (BW) [OVX+OPL (150)]; or (5) 300 mg OPL /kg BW [OVX+OPL (300)] in the drinking water. The Morris Water Maze (MWM) analysis was used to test cognition in the ovariectomized rats. Anxiety was determiend by measuring corticosterone (CORT) and estradiol (E2) levels in the blood serum, as compared to the normal control group. Determination of CA1 pyramidal cells of the hippocampus was performed on the brain,whereas the bone loss analysis was conducted by measuring the weight of femur and tibia calcium levels, together with histopathological observations. The results of MWM showed the effects of long-term memory (LTM) and short-term memory (STM), were significantly different for all groups throughout the study. During the second and third months, the STM was significantly higher in the [OVX+OPL (300) and (150)], as well as OVX+GT. The OVX group took the longest time to reach the hidden platform indicating decreasing STM. The OVX+GT rats had the significantly highest level of LTM as compared to the other groups. The histopathology observation on the CA1 hippocampal pyramidal cells showed significant decrease in the OVX group as compared to the other groups. The serum CORT and E2 serum level were significantly different between the groups; with GT exhibiting the lowest CORT level during the three months followed by OVX+OPL (300) and (150). Meanwhile, the OVX group had the highest CORT level from the first to the second month. All the groups showed an increase in their E2 from zero to the third month. Finally, the phytoestrogenic OPL dose dependently enhanced OVX bone-density, calcium contents, ash weights and T-ALP to above even the normal rats and improved bone structure. The findings from this study support the hypothesis that, the OPL dose dependently improved the cognitive functions and decreased anxiety of the estrogen deficient OVX rats towards normal control rats. The OPL dose dependently improved bone calcium density, significantly over the normal rats. The OPL treatments could prevent several maladies related to estrogen deficiency.